1976
DOI: 10.1063/1.322980
|View full text |Cite
|
Sign up to set email alerts
|

Electrical effects of SiC inclusions in EFG silicon ribbon solar cells

Abstract: The electrical effects of included silicon carbide (SiC) particles in edge-defined film-fed grown silicon ribbons have been examined. By employing a scanning electron microscope operated in the electron-beam-induced current mode, as well as observing the effects of SiC particles on solar-cell characteristics, the electrical activity of particles and particle-generated defects were studied. The influence of SiC particles largely appears to be a result of impurity accumulation around them rather than a direct ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…[ 52 ] Additionally, it has been reported that SiC inclusions act as impurity collection centers in the space–charge region, also reducing FF . [ 31 ] Since modules M3 and M4 show the highest J 02 recombination, they likely have higher recombination at/near the junction, either due to structural defects or impurities like SiC inclusions. It should be noted that these defects likely impacted the initial performance of the modules more than the degradation behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 52 ] Additionally, it has been reported that SiC inclusions act as impurity collection centers in the space–charge region, also reducing FF . [ 31 ] Since modules M3 and M4 show the highest J 02 recombination, they likely have higher recombination at/near the junction, either due to structural defects or impurities like SiC inclusions. It should be noted that these defects likely impacted the initial performance of the modules more than the degradation behavior.…”
Section: Resultsmentioning
confidence: 99%
“…[ 29,30 ] Silicon carbide particles occurring as inclusions can also lead to impurity accumulation. [ 31 ] Like most polycrystalline absorbers, the combination of grain boundaries, dislocations, and impurities acts as deep‐level Shockley–Read–Hall recombination centers that limit the bulk carrier lifetime ( τ normalb ) and diffusion length. This ultimately leads to an increase in the saturation current density ( J 0 ) of the cell and subsequent drop in open‐circuit voltage ( V OC ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their affinity to build stable, mesoscopic crystals with silicon, carbon and nitrogen have important impact on the material properties. SiC precipitates in Si solar cells (in this case in edge‐defined film‐fed grown (EFG) ribbon solar cells) have been found already in 1976 . The sources of carbon detected in the Si material were found to stem from graphite parts of the crystallization furnaces some years later.…”
Section: Historical Overview – a Coarse Chronology Of Research On Sicmentioning
confidence: 99%
“…In mc‐Si grown by the directional solidification method, it has been shown that grain boundaries 3, dislocations 4–15, impurities 16, 17 and foreign inclusions 18–23 negatively affect the PV performance of mc‐Si solar cells. It is desirable for the grain sizes of mc‐Si ingots to be as large as possible so that fewer grain boundaries will exist in mc‐Si wafers.…”
Section: Introductionmentioning
confidence: 99%